Perceptions of climate variability and dairy farmer adaptations in Corangamite Shire, Victoria, Australia. Issue 1 (2014) - ,; ,
Abstract : Purpose – The article surveys dairy farmers' lay knowledge of climate change and the adaptation strategies they have implemented to respond to climatic and economic drivers. Dairy farming is highly dependent on local weather and climate. The case study is in Western Victoria, Australia, part of a major dairy farming region that contributes 26 per cent of national milk production and 86 per cent of the country's dairy exports. The paper aims to discuss these issues.Design/methodology/approach – This study utilised a survey and semi‐structured interviews in Corangamite Shire, to document dairy farmers' perceptions of climate variability and the adaptation strategies they have implemented, compared to meteorological data collected on climate variability in the recent past.Findings – Farmers in this region perceive a change in rainfall and temperature broadly in line with meteorological records. Those that have experienced a greater degree of climate variability in drier regions were found to perceive it more accurately. Almost all respondents had already made changes to their dairy businesses, but in doing so only a small percentage were responding directly to seasonal variability or to longer term changes (9 and 15 per cent, respectively); the majority said they were responding to changing economic conditions in the industry.Originality/value – A primary survey of dairy farming adds to knowledge of how climate variability is perceived, and how it is adapted to in a region heavily reliant on rainfall for its prime economic activity. Acknowledgements : The authors would like to thank all the survey respondents for their kind participation and three reviewers. For assistance with survey distribution; Murray Goulburn Cooperative Co. Ltd, Warrnambool Cheese and Butter, and West Vic Dairy. For data and advice; Stephen Commadeur at Australian Agribusiness Group, and Helen Chenoweth and Graeme Anderson at the Victorian Department of Primary Industries.